2019
DOI: 10.1111/hiv.12791
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of blood telomere length in antiretroviral treatment‐naïve HIV‐positive participants enrolled in the NEAT 001/ANRS 143 clinical trial

Abstract: Objectives Our aim was to investigate factors associated with baseline blood telomere length in participants enrolled in NEAT 001/ANRS 143, a randomized, open‐label trial comparing ritonavir‐boosted darunavir (DRV/r) plus raltegravir (RAL) with DRV/r plus tenofovir disoproxil fumarate/emtricitabine (TDF/FTC) in antiretroviral therapy (ART)‐naïve HIV‐positive adults. Methods A cross‐sectional study of 201 randomly selected participants who had stored samples available was carried out. We measured telomere lengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 29 publications
0
9
1
Order By: Relevance
“…Compared to uninfected adults, PLWH have shorter leucocyte TL; which negatively correlates with viral load in untreated patients ( Table 2 ). 59 , 60 This TL attrition is pronounced and occurs rapidly after seroconversion, 61 , 62 Early introduction of ART partially recovers leucocyte TL because of the immune reconstitution process that shifts towards less differentiated cells with longer TL. 63 This positive effect of ART on TL, diminishes when ART initiation is delayed.…”
Section: Molecular and Cellular Biomarkers In Hiv Ageingmentioning
confidence: 99%
“…Compared to uninfected adults, PLWH have shorter leucocyte TL; which negatively correlates with viral load in untreated patients ( Table 2 ). 59 , 60 This TL attrition is pronounced and occurs rapidly after seroconversion, 61 , 62 Early introduction of ART partially recovers leucocyte TL because of the immune reconstitution process that shifts towards less differentiated cells with longer TL. 63 This positive effect of ART on TL, diminishes when ART initiation is delayed.…”
Section: Molecular and Cellular Biomarkers In Hiv Ageingmentioning
confidence: 99%
“…Telomere length shortening progressively occurs with aging and is linked to age-related diseases [36]. Recent findings demonstrate a higher extent of telomere length shortening observed in untreated HIV is associated with both age and viral load [37]. Although ART regimens, including those containing tenofovir, could impact telomere length by affecting telomerase activity [38], progressive telomere length shortening is associated with delaying ART initiation [39].…”
Section: Biological Aging Hallmarksmentioning
confidence: 99%
“…Untreated HIV infection and ageing had a synergistic effect on telomere shortening. It was calculated that a viral load of >100,000 copies/mL of blood plasma affected telomere length similarly to 7 years of ageing and concluded that an HIV-infected person with a viral load >100,000 copies/mL compared to an HIV-negative person with the same chronological age could have the telomere length of a person almost two decades older [ 28 ]. Untreated HIV infection will progress.…”
Section: Introductionmentioning
confidence: 99%
“…To understand the progression of HIV infection, the number of CD4+ T cells is monitored [ 29 ]. The number of CD4+ T cells < 200 cells/µL was associated with shortened telomeres [ 28 ]. The parameter often used to track inflammation [ 30 ] and the progression of HIV infection [ 29 ] is C-reactive protein (CRP).…”
Section: Introductionmentioning
confidence: 99%